2021
DOI: 10.1002/marc.202000703
|View full text |Cite
|
Sign up to set email alerts
|

Benzo/Naphthodifuranone‐Based Polymers: Effect of Perpendicular‐Extended Main Chain π‐Conjugation on Organic Field‐Effect Transistor Performances

Abstract: For polymer semiconductors, the backbone structure plays an essential role in determining their physicochemical properties and charge transport behaviors. In this work, two donor–acceptor‐type polymers (P‐BDF and P‐NDF) based on benzodifuranone (BDF) and naphthodifunarone (NDF) as electron‐deficient moieties and indaceno‐dithiophene as electron‐rich groups are designed, synthesized and, for the first time, applied in organic field‐effect transistor. P‐BDF and P‐NDF differ from their backbone structures while P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…[44][45][46][47] On the other hand, coplanarity may easily induce J-type aggregation. [48,49] A significant aggregation in the solid state can negatively influence the performance of these NFAs in photovoltaics (see Section 2.4), as expected based on earlier reports. [50,51] The films of TPA-T-INCN, TPA-2T-INCN, and TPA-2T-BAB blends with P3HT exhibit a wide absorption between 350 and 650 nm (Figure 2d).…”
Section: Optical and Electrochemical Propertiessupporting
confidence: 73%
“…[44][45][46][47] On the other hand, coplanarity may easily induce J-type aggregation. [48,49] A significant aggregation in the solid state can negatively influence the performance of these NFAs in photovoltaics (see Section 2.4), as expected based on earlier reports. [50,51] The films of TPA-T-INCN, TPA-2T-INCN, and TPA-2T-BAB blends with P3HT exhibit a wide absorption between 350 and 650 nm (Figure 2d).…”
Section: Optical and Electrochemical Propertiessupporting
confidence: 73%
“…Recently, Deng et al (2018) introduced S and F atoms to adjust the polymer backbone and obtained a polymer with hole mobility up to 0.65 cm 2 V −1 s −1 . Zhang et al then reported that the main chain coplanarity of polymer semiconductors is more essential than the sole extension of π-conjugation (especially perpendicularly to polymer main chains) after investigating two benzo/naphtodifuranone-based polymers ( Figure 1G ) ( Li et al, 2021 ). The same group also found that substituting the oxygen atoms for sulfur atoms in the diketopyrrolopyrrole core could not only improve the charge transfer mobility, but also convert p-type materials into ambipolar type semiconductors ( Figure 1H ) ( Zhang et al, 2018c ; Zhang et al, 2019a ).…”
Section: Organic Field Effect Transistormentioning
confidence: 99%
“…In a TAS molecule, the well‐matched D‐D‐D (donor‐donor‐donor) alignment provides a highly planar molecular backbone and extended π‐conjugation, which favor the efficient hole transfer within the individual molecule as well as between the adjacent molecules. [ 18 ] In addition, the sulfur atom contained in the functional group can modify the perovskite surface via dipole intermolecular interaction between a lone pair and Pb 2+ , when TAS is used as a dopant‐free HTM in n‐i‐p PSCs. Based on our theoretical and experimental results, TAS exhibits remarkably enhanced hole extraction, hole transport, and device performance compared to TAO and DAS.…”
Section: Introductionmentioning
confidence: 99%